Clinical imaging features and outcomes of intrathyroidal thymic carcinoma: an analysis of fourteen patients at a single medical institution - Gu, Lingling; Zhang, Lanfang; Huang, Wenxuan; Song, Xue; Xie, Xiaodong; Ding, Deqin (Frontiers in Oncology, 2025)
ObjectiveTo summarize the clinical characteristics and imaging features of intrathyroid thymic carcinoma (ITTC), along with diagnostic and therapeutic approaches, to increase awareness of this rare disease.MethodsWe retrospectively analyzed 14 patients with ITTC confirmed by core needle biopsy (CNB) and surgery combined with immunohistochemistry. The clinical and imaging findings, treatment, pathological findings and follow-up data of these patients were reviewed.ResultsThirteen patients were newly diagnosed and one relapsed at the original surgical site. All tumors were solitary, mostly located in the lower neck or upper chest, often in the tracheoesophageal groove with or without extension to the thyroid’s lower pole, and approximately two-thirds of patients presented with hoarseness. On CT, most lesions appeared as irregular, low-density soft-tissue masses, with calcification in two cases; contrast-enhanced CT revealed mild heterogeneous or homogeneous enhancement, and over half exhibited an arc-shaped interface with adjacent thyroid tissue. Most tumors were locally advanced, invading muscles, the supraclavicular fossa, tracheoesophageal groove, esophagus, tracheal wall, or mediastinal vessels. The diagnostic accuracy of fine-needle aspiration biopsy (FNAB) was low, whereas core needle biopsy (CNB) combined with immunohistochemistry was reliable. Ten patients underwent radical surgery, of whom three received adjuvant chemoradiotherapy and four adjuvant radiotherapy; four patients received radical chemoradiotherapy, and one received combined therapy including anlotinib, a novel tyrosine kinase inhibitor. The median follow-up was 86 months (range, 25–146), and three surgically treated patients developed local recurrence or pulmonary metastasis.ConclusionCNB combined with immunohistochemistry is recommended when the characteristic and imaging manifestations suggest a diagnosis of ITTC. Especially for locally advanced cases, imaging-based diagnosis can be useful for analysis and to guide treatment.